Educational gamification as a motivational strategy for teaching in primary education - Zambrano Barreiro, Mariana Natasha; Cevallos Cedeño, Ángela María (International Journal of Psychosocial Rehabilitation, 2020)
Currently, the teaching-learning process must be sufficiently stimulating and motivating, so that primary school students attract their interest in learning the different program content, so teachers must employ different techniques that succeed in stimulating and attracting them to the achievement of learning results, one of them being educational gamification. The objective of this work is to carry out a characterization of the educational Gamification strategy and its application as a tool for the motivation of primary education students. Use Desk Research methodology, which allowed for a systematic review of previous research on the subject. Finding that the Gamification strategy allows, through the incorporation of new technologies, the use of the underlying culture in digital natives, promoting motivation in them, being attractive at early ages at the level of primary education, the planned dynamics, They allow the transforming involvement of the student, creating an increase in motivation for the role that they have to play in the educational activity.